2019
DOI: 10.11646/zootaxa.4646.1.7
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomic revision of the genus Anostomoides (Characiformes: Anostomidae)

Abstract: A taxonomic revision of Anostomoides is herein presented based on a comprehensive revision of specimens deposited in fish collections and the literature. The present revision proposes that A. laticeps is a junior synonym of A. atrianalis, while A. passionis is a junior synonym of Leporinus nattereri, and the latter is thus transferred to Anostomoides, forming the new combination Anostomoides nattereri. Principal Components Analysis (PCA) showed that examined specimens form two distinct morphotypes, corroborati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 966 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Among the Anostomidae, premaxillary symphyseal teeth with a massive unicuspid incisiform shape are characteristics of Megaleporinus, of which eleven species are recognized (Ramirez et al 2017;Birindelli et al 2020). In contrast, Abramites, Anostomoides, and Leporinus have compressed teeth with a mesial ridge and usually a single outstanding cusp, often accompanied by smaller lateral cusps in juveniles (see Birindelli et al 2013;Assega and Birindelli 2019). Our comparisons suggest also that the specimens AMU-CURS-851 resemble the premaxillary symphyseal teeth of Megaleporinus muyscorum in size and morphology (Fig.…”
Section: General Description Comparisons and Remarksmentioning
confidence: 65%
“…Among the Anostomidae, premaxillary symphyseal teeth with a massive unicuspid incisiform shape are characteristics of Megaleporinus, of which eleven species are recognized (Ramirez et al 2017;Birindelli et al 2020). In contrast, Abramites, Anostomoides, and Leporinus have compressed teeth with a mesial ridge and usually a single outstanding cusp, often accompanied by smaller lateral cusps in juveniles (see Birindelli et al 2013;Assega and Birindelli 2019). Our comparisons suggest also that the specimens AMU-CURS-851 resemble the premaxillary symphyseal teeth of Megaleporinus muyscorum in size and morphology (Fig.…”
Section: General Description Comparisons and Remarksmentioning
confidence: 65%
“…Prior to the present study, three Leporinus species were considered to be present in the hydrographic basins of the Brazilian state of Maranhão— L. affinis , in the Itapecuru basin( Abreu et al, 2019 ), L. friderici in the Itapecuru, Mearim, Maracaçumé, Munim, Periá, and Parnaíba basins ( Piorski et al, 1998 ; Soares, 2005 ; Ramos, Ramos & Ramos, 2014 ; Melo et al, 2016 ; Abreu et al, 2019 ; Brito et al, 2019 ; Brito et al, 2020 ; Guimarães et al, 2021a ; Guimarães et al, 2021b ; Guimarães et al, 2021c ), and L. piau in the basins of the Itapecuru, Mearim, Turiaçu, and Parnaíba rivers ( Barros, Fraga & Birindelli, 2011 ; Ramos, Ramos & Ramos, 2014 ; Ribeiro et al, 2014 ; Assega & Birindelli, 2019 ; Abreu et al, 2019 ). Based on analyses of molecular data, however, Fraga et al (2014) and Nascimento et al (2016) found evidence of two distinct lineages in the L. piau group from the Itapecuru basin, while in the present study, L. piau was assigned to three different clades, being associated strongly with L. cf.…”
Section: Discussionmentioning
confidence: 99%